Um olhar sobre o sujeito em Paulo Freire: concepção e análise das obras Pedagogia do Oprimido, Pedagogia da Esperança e Pedagogia da Autonomia - Marini, Larissa Marcela (Universidade Federal de São Carlos, 2019)
The study of the subject in the current brazilian educational context is fundamental, because it occupies central position in the educative process, in order to guide the relations of teaching and learning established from the philosophical and sociological understanding that falls upon the subject. This conception about the subject of which one intends to develop reflects directly in educational practices present in classrooms throughout the country, and its discussion in the current context becomes essential considering the different proposals that have emerged in this scenario. Given this information, in light of a liberating and problematizing Theory of Education, whose notoriety is recognized in national and international context, this master’s degree research in Education proposed the in-depth study of the conception of subject in a Freirean approach, from the analysis of three works produced in different historical periods The selection criteria of the works were delineated based on the number of occurrences of the concept studied, the historical period of each work, as well as their relevance, being defined: Pedagogy of the Oppressed (1968 / 2014a), produced in Chile in his exile time; the Pedagogy of Hope: a reunion with the Pedagogy of the Oppressed (1992/2016), written in Brazil at a time of re-signification of the learning acquired from his journey around the world; and the Pedagogy of Autonomy (1996 / 2014b), as the last work produced in life by the educator. Our methodological approach was focused first on the bibliographic research described mainly by Salvador (1978), as well as Lima and Mioto (2007), and after was applied the content analysis of Bardin (2016) to treat and analyze the data from study of the subject as a record unit. In view of the above, this research presented the following central question: How is the subject conception constructed by Paulo Freire considering the study of three works produced in different periods of his career? The question is based on the hypothesis that the educator, despite influencing different philosophical currents in his thinking, constructs a specific subject conception in his pedagogy, which changes according to the historical moments of his production. In this way, it is outlined as a general objective: To identify and analyze the possible changes occurred in the conception of subject from the study of works produced in different periods of his trajectory, to verify its affirmation as a conceptual category defined by Paulo Freire, considering that the social and historical context are important elements of his production. It is expected that the study bring contribution to orientate educational practices to more democratic ways that considers the students as subjects of the process.
Keywords: Sujeito; Educação; Paulo Freire; Subject; Education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM